2020
DOI: 10.1111/hiv.13023
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical factors associated with immune reconstitution in HIV/HBV co‐infected and HIV mono‐infected patients: a retrospective cohort study

Abstract: Objectives To describe the clinical characteristics and factors associated with CD4 T‐cell count and CD4/CD8 ratio restoration in HIV mono‐infected and HIV/HBV co‐infected individuals, and to explore liver and renal functional changes in both groups. Methods A retrospective cohort study was performed including 356 HIV/HBV co‐infected and 716 HIV mono‐infected participants who initiated antiretroviral therapy (ART) during 2013–2017 in Beijing Youan Hospital, China. Demographic and clinical characteristics were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Indeed, mounting evidence [22,[29][30][31] shows low baseline CD4 + T cell count negatively impacts long-term CD4 + T cell recovery in both amount and functionality, affecting the progression of HIV infection. In addition, Jiang et al [32] found that baseline HIV VL is signi cantly associated with CD4 + T cell restoration among PLWH. However, no matched conclusion was obtained from our data.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mounting evidence [22,[29][30][31] shows low baseline CD4 + T cell count negatively impacts long-term CD4 + T cell recovery in both amount and functionality, affecting the progression of HIV infection. In addition, Jiang et al [32] found that baseline HIV VL is signi cantly associated with CD4 + T cell restoration among PLWH. However, no matched conclusion was obtained from our data.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mounting evidence [22,[32][33][34] shows low baseline CD4 + T cell count negatively impacts longterm CD4 + T cell recovery in both amount and functionality, affecting the progression of HIV infection. In addition, Jiang et al [35] found that baseline HIV VL is significantly associated with CD4 + T cell restoration among PLWH. However, because we did not include the baseline VL but choose VL after 2 years treatment, no matched conclusion was obtained from our data.…”
Section: Discussionmentioning
confidence: 99%